2011
DOI: 10.1007/s12668-011-0002-9
|View full text |Cite
|
Sign up to set email alerts
|

New Insight on Bio-sensing by Nano-fabricated Memristors

Abstract: We report here on a new insight for biosensing based on the memristive effect of functionalized Schottky-barrier memristive silicon nanowire in dry environment. The device concept is discussed. Electrical measurements confirm the bio-detection by the narrowing of the memristive I ds − V ds hysteresis upon interaction of antigen with antibody-functionalized nanowire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 10 publications
1
52
0
Order By: Relevance
“…3. In previous papers, we demonstrated that a voltage gap measured in between the forward and backward current minima appears when biomolecules are immobilized onto the nanowire surface, and its changes are used for the detection of increasing concentrations of analytes [25,26]. In the present letter, we show that the memristive voltage gap variation also works for pH measurements.…”
Section: Ph Sensing In Airsupporting
confidence: 51%
See 1 more Smart Citation
“…3. In previous papers, we demonstrated that a voltage gap measured in between the forward and backward current minima appears when biomolecules are immobilized onto the nanowire surface, and its changes are used for the detection of increasing concentrations of analytes [25,26]. In the present letter, we show that the memristive voltage gap variation also works for pH measurements.…”
Section: Ph Sensing In Airsupporting
confidence: 51%
“…In these structures, the memory effects depend on charge carrier rearrangement at the nanoscale as due to external perturbations [24]. Recently, very promising results have been reported on the use of the memristive behavior of SiNWs for sensing biological molecules in dry conditions [25,26], thus opening a promising new research line. These devices have been characterized [26,27] and demonstrated to feature the main fingerprints of a memristive system, such as the dynamic current-voltage curves of a pronounced double loop shape, the pinched hysteresis-loop, and its frequency-dependence [22].…”
Section: Introductionmentioning
confidence: 99%
“…When biological substances are present on the surface of the device the hysteresis appears shifted from zero to different voltage values, namely a voltage gap is introduced in the semi-logarithmic electrical characteristics, leading to a label-free bio-detection method [4], [5].…”
Section: A Experimental -Fabrication Methodologymentioning
confidence: 99%
“…Among the different applications that memristive effect had already been introduced, a further approach presuming upon the memristive behavior of bio-functionalized nanofabricated wires, so-called Memristive Biosensors, has been suggested for sensing biomolecules [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…Typically the currently developed SiNW biosensors require measurement with a probe station to monitor the conductance changes between source and drain electrodes induced by recognition event between target molecules and the surface-bound receptors. We have very recently introduced a completely novel approach based on the memristive effect in SiNWs [3], [4], [5], and have demonstrated great potentials for the ultra-high sensitive detection of biomarkers in air [6]. This method is based on charge effects of biomolecules on the so called voltage gap.…”
Section: Introductionmentioning
confidence: 99%